Overview of birch triterpenes - Nguyen, Thị Thu Thảo; Huynh, Lời (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2025)
Epidermolysis bullosa (EB) is an inherited disease of the skin that makes the skin very fragile and causes severe blistering and scarring. Birch triterpene (BT) is used in two types of Epidermolysis bullosa including dystrophic Epidermolysis bullosa (DEB) and junctional Epidermolysis bullosa (JEB), to treat skin wounds. These are wounds where the upper layers of the skin have been damaged. Birch triterpene is indicated for the treatment of partial thickness wounds associated with dystrophic and junctional EB in people aged six months of age and older. The FDA (US Food and Drug Administration) considers it to be a first-in-class medication. This review was to disscus the chemical composition, clinical studies, uses of birch triterpenes.